The effect of information booklets on family members' satisfaction with decision making in an intensive care unit of Malaysia - Hamidah, Othman; Haszalina, Hassan; Mainul, Haque (EManuscript Services, 2016)
Background: To test the effect of information booklets on family members’ satisfaction with decision-making around the care of critically ill patients in an intensive care unit.